DC3 is eight-wheels locomotive with the second method of traction ratio, rating of discharging loads and additional ones of its wheels and deflections of spring suspension during the tractions efforts transfer from bogies to car body with using reclining - Bratash, V. A.; Yefimova, T. I.; Povolotska, U. Y. (Science and Transport Progress, 2011)
In the article the calculation formulas for determination of unloadings (finish loadings) of wheels and bendings of a spring suspension of eight-wheel electric locomotive DS3 with the traction transmission of the second kind at transmitting the traction forces from bogies to body by means of sloping rods are presented. The numeral calculations on the example of main line freight-and-passenger electric locomotive DS3 are performed.